Short-term effects of a 8-weeks whole-body vibration protocol on muscle strength and flexibility in female professional athletes - Fagnani, F.; Giombini, A.; Di Salvo, V.; Parisi, A.; Pigozzi, F. (12th Annual Congress of the European College of Sport Science, Jyväskylä, Finland - July 11-14th 2007, 2007)
Objective: This randomized controlled study was designed to investigate the short term effects of a 8 weeks whole body vibration protocol on muscle performance and flexibility in female professional athletes. Design: Twenty six young volunteers female athlete (aged 21-27 yr) were randomized to either the vibration group or control group. The vibration-intervention consisted of a 8 weeks WBV 3 times a week employed by standing on a vertically vibration platform. As outcome measures two performance tests (counter-movement jump, extension strength of lower extremities with an isokinetic horizontal leg press, and a sit and reach test for flexibility were performed initially and after 8 weeks. Results: 24 athletes completed the study properly. In the experimental group (N=13) WBV induced significant improvement of bilateral knee extensor strength (P<.001), counter-movements jump (P<.001) and flexibility (P<.001) after 8 weeks training. No significant changes were found for all the outcome measures for the control group (N=11). Conclusions: WBV is a suitable training method to improve knee extension maximal strength, counter-movement jump and flexibility in young female athlete if it is properly designed. Not only the optimal frequency, amplitude and gforces need to be identified but also the level of muscle activation that would benefit more from vibration stimulation.